Design and Implementation of an Autonomous Robot Soccer System. (3rd May 2013) - Wong, Ching-Chang; Cheng, Chi-Tai; Chan, Hsiang-Min
Abstract A design and implementation method of a robot soccer system with three vision-based autonomous robots is proposed in this paper. A hierarchical architecture with four independent layers: (a) information layer, (b) strategy layer, (c) tactics layer, and (d) execution layer, is proposed to construct a flexible and robust vision-based autonomous robot soccer system efficiently. Five mechanisms, including (a) a two-dimensional neck mechanism, (b) dribbling mechanism, (c) shooting mechanism, (d) aiming mechanism, and (e) flexible movement mechanism, are proposed to mean the robot with multiple functions can win the game. A method based on data obtained from a compass and a vision sensor is proposed to determine the location of the robot on the field. In the strategy design, a hierarchical architecture of decision based on the finite-state transition mechanism for the field players and the goalkeeper is proposed to solve varied situations in the robot soccer game. Three vision-based robots are implemented and some real competition results in the FIRA Cup are presented to illustrate the validity and feasibility of the proposed method in autonomous robot soccer system design.